Benzene Ring Knitting Achieved by Ambient‐Temperature Dehalogenation via Mechanochemical Ullmann‐Type Reductive Coupling. Issue 21 (19th April 2021) - Chen, Hao; Fan, Juntian; Fu, Yuqing; Do‐Thanh, Chi‐Linh; Suo, Xian; Wang, Tao; Popovs, Ilja; Jiang, De‐en; Yuan, Yating; Yang, Zhenzhen; Dai, Sheng
Abstract: The current approaches capable of affording conjugated porous networks (CPNs) still rely on solution‐based coupling reactions promoted by noble metal complexes or Lewis acids, on‐surface polymerization conducted in ultrahigh‐vacuum environment at very high temperatures (>200 °C), or mechanochemical Scholl‐type reactions limited to electron‐rich substrates. To develop simple and scalable approaches capable of making CPNs under neat and ambient conditions, herein, a novel and complementary method to the current oxidative Scholl coupling processes is demonstrated to afford CPNs via direct aromatic ring knitting promoted by mechanochemical Ullmann‐type reactions. The key to this strategy lies in the dehalogenation of aromatic halides in the presence of Mg involving the formation of Grignard reagent intermediates. Products (Ph‐CPN‐1) obtained via direct CC bond formation between 1, 2, 4, 5‐tetrabromobenzene (TBB) monomer feature high surface areas together with mesoporous architecture. The versatility of this approach is confirmed by the successful construction of various CPNs via knitting of the corresponding aromatic rings (e.g., pyrene and triphenylene), and even highly crystalline graphite product was obtained. The CPNs exhibit good electrochemical performance as the anode material in lithium‐ion batteries (LIBs). This approach expands the frontiers of CPN synthesis and provides new opportunities to their scalable applications. Abstract : Construction of conjugated porous networks (CPN) is realized via straight‐forward aromatic ring knitting derived from reductive dehalogenation of aromatic halides promoted by mechanochemical Ullmann‐type reactions in the presence of magnesium under neat and ambient conditions.